2022
DOI: 10.1039/d2tb00289b
|View full text |Cite
|
Sign up to set email alerts
|

MXenes: state-of-the-art synthesis, composites and bioapplications

Abstract: MXenes have shown great potential in a variety of domains. This review elaborates the up-to-date synthesis methods, physicochemical properties and biological applications of MXene-based nanocomposites, as well as the practical hurdles and prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 164 publications
(253 reference statements)
0
4
0
Order By: Relevance
“…), 'X' for carbon or nitrogen, and 'T x ' represents the terminal groups like F, Br, O, S, and OH. To date, a variety of MXenes have been fabricated, including Ti 3 C 2 , Ti 2 C, and Nb 2 C. 200,201 The large specific surface area and suitable optical and electronic characteristics make MXenes the most promising emerging materials in the field of photocatalysis. Moreover, good conductivity due to conducting nuclei in multilayer structures and various terminating functional groups makes MXenes promising photocatalysts.…”
Section: Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…), 'X' for carbon or nitrogen, and 'T x ' represents the terminal groups like F, Br, O, S, and OH. To date, a variety of MXenes have been fabricated, including Ti 3 C 2 , Ti 2 C, and Nb 2 C. 200,201 The large specific surface area and suitable optical and electronic characteristics make MXenes the most promising emerging materials in the field of photocatalysis. Moreover, good conductivity due to conducting nuclei in multilayer structures and various terminating functional groups makes MXenes promising photocatalysts.…”
Section: Mxenesmentioning
confidence: 99%
“…), ‘X’ for carbon or nitrogen, and ‘T x ’ represents the terminal groups like F, Br, O, S, and OH. To date, a variety of MXenes have been fabricated, including Ti 3 C 2 , Ti 2 C, and Nb 2 C. 200,201…”
Section: Library Of Materials Used For Heterojunction Formation In Ph...mentioning
confidence: 99%
“…Hence, MXenes have been studied for use in tumor ablation and cancer therapy. Owing to their surface plasmon resonances, they display efficacious near-infrared light absorption and intense photothermal conversion [ 62 ].…”
Section: Properties Of Mxenesmentioning
confidence: 99%
“…The abundant functional groups on its surface give it more abundant physical and chemical properties and biological properties. MXene has good biocompatibility, electrical conductivity and mechanical properties, but also can produce photothermal effect under NIR conditions, which makes it widely used in biological fields such as biosensing, tumor therapy, tracer imaging and so on ( Naguib et al, 2012 ; Carey and Barsoum, 2021 ; Chen et al, 2021 ; Fadahunsi et al, 2022 ). In addition, researchers also found that MXene has good antibacterial activity and certain scavenging ability of active oxygen species ( Jastrzębska et al, 2017 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%